Disaffiliierende Bewertungen und Haltungsbekundungen in Er-zählaktivitäten – eine multimodale Analyse - Bröker, Sophie; Zima, Elisabeth (Linguistik Online, 2022)
This paper deals with multimodal displays of non-affiliative stances and assessments in face-to-face triadic storytelling activities. Building on conversational analytical research that has highlighted the co-constructed nature of storytelling activities and the intersubjective nature of stance-taking, this paper takes a multimodal perspective and focusses on how interactants use language, prosody, gaze, and gestures to express stances that are non-affiliative to different degrees. The paper addresses two issues: We first concentrate on the ways that disaffiliative assessments and stances are communicated as multimodal packages before zooming in on the ways that storytellers and recipients deal with displays of disaffiliation. This includes both verbal and nonverbal strategies to highlight disaffiliation and interactional work to jointly mitigate it. By its focus on multimodal stance-taking in storytelling activities, the paper ties in with both the recently growing interest in the multimodal nature of stance-taking as well as recent pleas to revisit interactional storytelling from a multimodal perspective.